First, we need to write the right side of the equation in standard form:
y = (x + 4)^2 + 4x^2 - 3x + 2
y = x^2 + 8x + 16 + 4x^2 - 3x + 2
y = 1x^2 + 4x^2 + 8x - 3x + 16 + 2
y = (1 + 4)x^2 + (8 - 3)x + (16 + 2)
y = 5x^2 + 5x + 18
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(5) for color(red)(a)
color(blue)(5) for color(blue)(b)
color(green)(18) for color(green)(c) gives:
x = (-color(blue)(5) +- sqrt(color(blue)(5)^2 - (4 * color(red)(5) * color(green)(18))))/(2 * color(red)(5))
x = (-color(blue)(5) +- sqrt(25 - 360))/10
x = (-5 +- sqrt(-335))/10